Can the tourism industry contribute to international adaptation finance? - Janto S. Hess; Pieter Pauw; Elissaios Papyrakis (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
At the UN climate negotiations, developed countries pledged to mobilise US 100 billion of climate finance per year from 2020 onwards to support developing countries in dealing with climate change. Since this money is supposed to come from private sources too – some of which is to be spent on climate change adaptation – this briefing paper explores the potential of the international tourism industry to contribute to adaptation finance, with a focus on Small Island Development States (SIDS). The SIDS is a group of low-lying coastal countries that are particularly susceptible to natural disasters and climate change impacts. Tourism is the main economic sector for most of them. Given the sector's vulnerability to climate change (e.g. rising sea levels or extreme weather events), high levels of investment in adaptation will be needed to maintain the high number of visitors. A diverse landscape of modalities for funding adaptation through the tourism sector is available, with corresponding limitations and challenges in their implementation. The tourism sector represents a diverse array of businesses. The adaptive capacities of these businesses, their operational scales and customer demands are key determining factors behind the potential to contribute to, or finance, adaptation. Different options are available on various scales. For example, on a local scale, hotels and resorts can contribute to adaptation by investing in sea walls, or in water- and energy-efficiency measures. Governments can endorse this through, for instance, building codes and policies for sustainable water and energy use. On a sub-national or national scale, adaptation funds (i.e. financed by public and private sources) or adaptation taxes could be suitable instruments for involving a range of private actors operating in tourism and generating financial resources. Insurance schemes could help to share in and deal with risks. Tourism enterprises can contribute to and invest in adaptation in SIDS. Regardless of whether such investments would count as part of the US 100 billion, we recommend governments in SIDS to endorse this. However, in developing such mechanisms to mobilise pri¬vate financial contributions, it must be considered that tourists and multinational tourism corporations have the highest adaptive capacities. They can simply change destinations if climate impacts are too extreme or if the costs of adaptation make a destination relatively more expensive. The price sensitivities of the industry thus need to be factored in, and taxes or levies should theoretically be applied as uniformly as possible across tourist destinations in different countries in order to prevent travellers from substituting more expensive destinations (where adaptation taxes are adopted) for cheaper ones.
Keywords: 330; Governance; Klimawandel